Bimetallic Palladium/Cobalt Catalysis for Enantioselective Allylic C−H Alkylation via a Transient Chiral Nucleophile Strategy. (3rd February 2022) - Wang, Hongkai; Xu, Yang; Zhang, Fangqing; Liu, Yangbin; Feng, Xiaoming
Abstract: An asymmetric allylic C−H functionalization has been developed by making use of transient chiral nucleophiles, as well as bimetallic synergistic catalysis with an achiral Pd 0 catalyst and a chiral N, N′‐dioxide‐Co II complex. A variety of β‐ketoesters and N‐Boc oxindoles coupled with allylbenzenes and aliphatic terminal alkenes were well tolerated, furnishing the desired allylic alkylation products in high yields (up to 99 %) with excellent regioselectivities and enantioselectivities (up to 99 % ee) . Abstract : An asymmetric allylic C−H functionalization has been developed by making use of transient chiral nucleophiles, as well as bimetallic synergistic catalysis with an achiral Pd 0 catalyst and a chiral N, N ′‐dioxide‐Co II complex. The corresponding allylated products could be obtained in moderate to good yields with excellent regio‐ ( l/b >20 : 1) and enantioselectivities (up to 99 % ee ) under mild reaction conditions.